Civic law and natural value: enforcing environmental ethics - Rolston, Holmes, 1932-2025, author; State Bar of California, Environmental Law Section, publisher (Colorado State University. Libraries, 2011)
How far can and ought environmental values can be protected and enforced by legislation? Environmental regulation extends from Acts of Congress to lighting campfires and enforcement is widespread. The environment is a commons and this necessitates a public ethic where humans have benefits and harms at stake and must act in concert for protection. Environmental legislation can and ought protect animals, species, and ecosystems as well as humans--sometimes ever defending these against basic human interests.
Keywords: environmental ethics; law; legislation; policy; enforcement; wilderness; public good; natural values; regulation; human rights; responsibility; nature